2022
DOI: 10.1002/qre.3180
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian and non‐Bayesian inference of Weibull lifetime model based on partially observed competing risks data under unified hybrid censoring scheme

Abstract: In this paper, a competing risk model is analyzed based on unified hybrid censoring scheme (UHCS). It is assumed that the latent failure times follow Weibull distributions with a common shape and different scale parameters. The maximum likelihood estimates (MLEs) and approximate confidence intervals (ACIs) of the distributional parameters are obtained. Sufficient conditions under which the MLEs exist (uniquely) have been studied. Further, the Bayes estimates are obtained with respect to symmetric and asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Average lengths (AL) of confidence intervals and coverage probabilities (CP) are used to make a comparison between the interval estimators. Using the method described in [26] , competing risks samples based on UPHC have been constructed.…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Average lengths (AL) of confidence intervals and coverage probabilities (CP) are used to make a comparison between the interval estimators. Using the method described in [26] , competing risks samples based on UPHC have been constructed.…”
Section: Simulation Studymentioning
confidence: 99%
“…The second direction involves the use of competing risks data under UHCS to estimate the parameters , and θ . For more details on recent studies using partially observed competing risks data, see [21] , [22] , [23] , [24] , [25] , [26] , and [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, for 𝜈 = 0 , it transforms into the Bayesian estimate relative to the SE loss function. Similarly, the Bayesian estimator under the BLINEX loss function, as depicted in (19), reduces to the maximum likelihood estimate at 𝜈 = 1 and corresponds to the asymmetric LINEX loss function at 𝜈 = 0. Likewise, under the BGE loss function in (20), the Bayesian estimator reduces to the maximum likelihood estimate at 𝜈 = 1 and corresponds to the GE loss function at 𝜈 = 0.…”
Section: The Bge Loss Functionmentioning
confidence: 99%
“…In reliability analysis, to get around the issue of model identifiability, many researchers assume that the causes of failure are independent. See, for example Panwar et al (2015), Ashour and Nassar (2017), Koley and Kundu (2017), Wang (2018), Wang and Li (2019), Mahto et al (2021), Dutta and Kayal (2022b), Dutta and Kayal (2022a) and Dutta et al (2023). However, in general, it is not easy to verify the assumption that the causes of failure are independent to each other.…”
Section: Introductionmentioning
confidence: 99%